Effect of Different Treated Techniques on Palm Oil Fuel Ash to The Physico-Mechanical Properties of Cement Paste - Sabari, Amirul Hafiz; Mohamad Zaky Noh (Enhanced Knowledge in Sciences and Technology, 2024)
An inquiry is being conducted to explore the potential utilisation of palm oil fuel ash (POFA) in cement concrete due to concerns about the adverse environmental and health consequences associated with its improper disposal. This study investigates the impact of different compositions of POFA (10 wt%, 20 wt%, 30 wt%, and 40 wt%) on concrete qualities when used as a replacement for normal Portland cement (OPC). The objective is to provide pragmatic guidance to analysts and manufacturers that are contemplating the integration of POFA into cement concrete as a means to mitigate apprehensions over environmental contamination. The physical parameters, including water absorption, bulk density, and compressive strength, were assessed using the Mettler Toledo density kit XS64 and a Universal Testing Machine. The findings demonstrate that the concrete containing 40 wt% TPOFA exhibited the lowest bulk density, with an average value of 1.700 g/cm³. Moreover, there was a constant reduction in bulk density as the concentration of POFA increased. The decrease in POFA content, with the exception of UPOFA, resulted in a reduction in water absorption, indicating an improved ability to resist moisture. The compressive strength increased notably as the TPOFA concentration increased, reaching an average value of 56.88 MPa with the maximum composition of 40 wt%. The enhancement in strength is ascribed to the pozzolanic characteristics of POFA, resulting in a prolongation of the cure period. The study’s findings offer useful insights for industry professionals who are looking for sustainable alternatives to OPC. These insights enable the efficient utilisation of POFA in cement concrete applications, while also resolving concerns regarding environmental disposal.